KETAHANAN PANGAN DALAM PENINGKATAN PEMBANGUNAN EKONOMI SERTA KAITANNYA DALAM PANDANGAN ISLAM - Zulaika Matondang (Institut Agama Islam Negeri Padngsidimpuan, 2016)
Development of food security subsystems rely heavily on food availability, food distribution and consumption of food. Sustainable food supply is essential to ensure food security in order not to fail. By supporting factor in land and good infrastructure is expected to increase food production through a diversity of foodstuffs. The availability of a diversity of foodstuffs strongly support the diversification of food in order to improve public nutrition, which helps to enhance the quality of human resources, which in turn is expected to increase Indonesia's economic development. Stock foodstuffs indispensable as access to ensure food security during such adverse conditions contained in the Qur'an Surah Yusuf verse 47 and verse 48 of Surah Yusuf always make savings when production is on the rise.